Cortical blindness and not optic neuritis as a cause of vision loss in a Sjögren's syndrome (SS) patient with the neuromyelitis optica spectrum disorder (NMOSD): Challenges of ascribing demyelinating syndromes to SS. Issue 34 (August 2017) - Lalji, Aliya; Izbudak, Izlem; Birnbaum, Julius
Abstract: Rationale: The conception that multiple sclerosis may be challenging to distinguish from demyelinating manifestations of Sjögren's syndrome (SS) was introduced more than 30 years ago. However, it is now recognized that the neuromyelitis optica spectrum disorder (NMOSD) may occur more frequently in SS as opposed to multiple sclerosis. Characteristic NMOSD features can include severe attacks of optic neuritis, myelitis which is frequently longitudinally-extensive (spanning at least three vertebral segments on magnetic resonance imaging [MRI]), and an association with anti-aquaporin-4 antibodies. In addition, whereas NMOSD was initially thought to spare the brain, it is now recognized that brain lesions occur in a majority of NMOSD patients. Therefore, it is important for the multi-disciplinary team of physicians who care for SS patients to understand this widening spectrum of NMOSD as encompassing brain lesions. In this case-report we describe clinical features, radiographic findings, and treatment of a SS NMOSD patient presenting with severely decreased visual acuity, visual hallucinations, and encephalopathy. Patient concerns: The SS NMOSD patient presented with rapid, bilateral onset of severely decreased visual acuity and was therefore suspected as having bilateral optic neuritis. Diagnosis: However, the patient lacked stigmata of optic neuritis, instead had visual hallucinations and encephalopathy suggestive of cortical blindness, and was noted to have occipital lobe lesions on brain MRI. Other radiographic findings included simultaneous enhancement of brainstem and periventricular lesions. Interventions: The patient was initially treated with methylprednisolone with no change in her neurological deficits. She was then treated with plasma exchange therapy. Outcomes: The patient had resolution of decreased visual acuity, visual hallucinations, encephalopathy, and contrast-enhancing brain lesions in response to plasma exchange therapy. Lesson: We provide the first example of severely decreased visual acuity in a NMOSD patient due to cortical blindness and not bilateral optic neuritis. This finding expands the spectrum of central nervous system syndromes and brain lesions which may occur in NMOSD. The synchronous enhancement of a brainstem lesion (known to occur in NMOSD) with occipital lobe lesions also suggests that our patient's occipital lobe findings were due to NMOSD. All of our patient's findings had an excellent clinical and radiographic response to plasma exchange therapy.